Haïti aujourd'hui, Haïti demain : regards croisés : actes du symposium organisé par l'École de développement international et mondialisation (ÉDIM), Université d'Ottawa, les 6 et 7 avril 2010 - Baranyi, Stephen, 1962-; Beaudet, Pierre, 1950-; Martinez, Andrea, 1955- (Les Presses de l'Universite d'Ottawa, 2011)
Haiti today, Haiti tomorrow brings together the testimonies and analyzes of academics, specialists and organizations from Canada and Haiti on the Haitian situation after the 2010 earthquake. The objective of the volume is to discuss ways of transforming the crisis into an opportunity to strengthen endogenous, equitable and sustainable development.